2004
DOI: 10.1116/1.1697482
|View full text |Cite
|
Sign up to set email alerts
|

Properties of C4F8 inductively coupled plasmas. I. Studies of Ar/c-C4F8 magnetically confined plasmas for etching of SiO2

Abstract: Articles you may be interested inEffect of gas mixing ratio on etch behavior of Zr O 2 thin films in B Cl 3 ∕ He inductively coupled plasma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 19 publications
3
21
0
Order By: Relevance
“…6, resemble those of ions measured in low pressure C 4 F 8 rf plasmas by Li et al 4,5 and Goyette et al 24 A primary principle governing our IRIS work is that the apparatus is designed to form molecular beams that contain virtually all of the species present in the plasma. 6, resemble those of ions measured in low pressure C 4 F 8 rf plasmas by Li et al 4,5 and Goyette et al 24 A primary principle governing our IRIS work is that the apparatus is designed to form molecular beams that contain virtually all of the species present in the plasma.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…6, resemble those of ions measured in low pressure C 4 F 8 rf plasmas by Li et al 4,5 and Goyette et al 24 A primary principle governing our IRIS work is that the apparatus is designed to form molecular beams that contain virtually all of the species present in the plasma. 6, resemble those of ions measured in low pressure C 4 F 8 rf plasmas by Li et al 4,5 and Goyette et al 24 A primary principle governing our IRIS work is that the apparatus is designed to form molecular beams that contain virtually all of the species present in the plasma.…”
Section: Discussionmentioning
confidence: 82%
“…Figures 2 and 3 show the intensities of the six major ions present in C 3 F 8 and C 4 F 8 plasma molecular beams as a function of P, with the source flow set at 10 SCCM ͑gas pressure ϳ45 mTorr͒. 4,5,24 There are two primary ways of analyzing these data: examining the shapes and widths of the distributions, and calculating the mean energy for the individual IEDs. 2.…”
Section: Resultsmentioning
confidence: 99%
“…This may be attributed to an increase in fluorine availability at the polymer surface since surface analytical studies have shown that the steady state FC film thickness changes little in this regime. 33 Increasing the flow of fluorocarbon growth precursors further leads to strongly increased FC deposition rates on the polymer substrates, which lowers the net etching rate further and ultimately causes a switchover to net FC film deposition at 80% C 4 F 8 . Figure 5͑a͒ also shows data for pure C 4 F 8 .…”
Section: B Effect Of Fluorocarbon Gas Addition To Ar Dischargesmentioning
confidence: 99%
“…10 The values for EY were obtained from the etch rate and the ion flux as stated in Eq. To see this, we rearranged our results from Sec.…”
Section: A Dependence Of Surface Roughness On Deposited Energy Densitymentioning
confidence: 99%